2022
DOI: 10.1213/ane.0000000000005944
|View full text |Cite
|
Sign up to set email alerts
|

Nonopioid Analgesics for the Perioperative Geriatric Patient: A Narrative Review

Abstract: Management of acute perioperative pain in the geriatric patient can be challenging as the physiologic and pharmacokinetic changes associated with aging may predispose older patients to opioid-related side effects. Furthermore, elderly adults are more susceptible to postoperative delirium and postoperative cognitive dysfunction, which may be exacerbated by both poorly controlled postoperative pain and commonly used pain medications. This narrative review summarizes the literature published in the past 10 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 163 publications
(341 reference statements)
0
4
0
Order By: Relevance
“… 50 Santosa et al conducted a retrospective analysis of patients being co-prescribed opiates with muscle relaxants and benzodiazepines, and found that patients were significantly more likely to refill their opioid prescriptions even after controlling for preoperative opioid exposure. 51 Caution must be exercised when using muscle relaxants in patients at high risk of postoperative complications, including older patients (age >65 years), 52 morbidly obese patients (BMI >40 kg/m 2 ), those with sleep apnea, and those with significant comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“… 50 Santosa et al conducted a retrospective analysis of patients being co-prescribed opiates with muscle relaxants and benzodiazepines, and found that patients were significantly more likely to refill their opioid prescriptions even after controlling for preoperative opioid exposure. 51 Caution must be exercised when using muscle relaxants in patients at high risk of postoperative complications, including older patients (age >65 years), 52 morbidly obese patients (BMI >40 kg/m 2 ), those with sleep apnea, and those with significant comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that non-narcotic analgesics may be the preferred approach to perioperative analgesia in the geriatric patient population ( Wilson et al, 2022 ) as opioid administration has been associated with increased rates of POCD ( Awada et al, 2019 ) and possibly POD ( Clegg and Young, 2011 ). Conversely, pain, especially severe pain, increases the risk for delirium [for review, see O’Gara et al (2021) ], and there is clearly a risk-benefit assessment that must be considered as opioid analgesics are highly effective in relieving acute pain.…”
Section: Managementmentioning
confidence: 99%
“…[1][2][3] Despite their benefits, caution should be exercised, particularly in geriatric patients, due to potential side effects. [4][5][6] Among the NSAIDs used during the perioperative period after TKA, ketorolac is commonly administered. This drug has shown efficacy in providing analgesia; however, evidence suggests a ceiling effect for its potency.…”
Section: Introductionmentioning
confidence: 99%
“…13 Despite their benefits, caution should be exercised, particularly in geriatric patients, due to potential side effects. 4–6…”
Section: Introductionmentioning
confidence: 99%